Strategi Komunikasi Amphuri dalam Membangun Citra Perusahaan pada Anggota - Rima Rachmaningsih; Halomoan Harahap (Jurnal Syntax Transformation, 2022)
Amphuri is an organization consisting of PIHK (Special Hajj Organizer) and PPIU (Umrah Organizing Company) in Indonesia is democratic, free, independent and responsible in handling the world of hajj and Umrah in the broadest sense and creating a conducive and competitive climate. The hope of this association is to have strong bargaining power in negotiating with Muassasah and various other stakeholders. One of the organizational communication strategies implemented by AMPHURI in building the company's image to members is to be a media liaison between members with the Government of the Republic of Indonesia, the Kingdom of Saudi Arabia and Stakeholders in Indonesia and Saudi Arabia. According to Peter R. Monge and Noshir S, Network Theory is "connectedness" or "connectedness" which is the idea that there is a relatively stable line of communication between individuals and members of the organization. Relationship Management Theory focuses on building or establishing mutually beneficial relationships in organizations, this theory is known as Organization Public Relationship (OPR) theory. According to Kriyantoni (2017), this OPR departs from the co-creational paradigm that considers communication is used to stimulate the public to jointly create meaning (co-creator meaning) and suppress it in building relationships with all public. Public Relations is an activity related to establishing good relations with the target public, PR establishing good communication to external and internal organizations. (Effendy, 2011). Research with this qualitative method looks at how influential organizational communication strategies are in building a company's image on members through case studies on AMPHURI work programs. The results of this research show that AMPHURI's work program is an organizational communication strategy implemented by AMPHURI to support the company's operations with the aim of creating an image in its member companies. AMPHURI's work program has been well received and run by members by following and supporting all work programs and training programs for its members.